Los verbos modales en español desde la perspectiva langackeriana - Adéla Smažíková (Studia Romanistica, 2022)
This article presents the problem of modal verbs in Spanish from the perspective of Langacker’s cognitive grammar. It focuses on the fundamental terms and deals with the problematic point of the theory: the temporal grounding of modal verbs. According to Langacker, grounding elements, in the strict sense of the word, do not reflect verb tense. Therefore, it can be deduced that in most of the languages with verb inflection, including Spanish, modal verbs cannot play this role. Despite this, it is argued that the nature and conceptual content of modal verbs is similar in Spanish and English and that it is possible to analyze modal verbs as grounding elements by redefining the ground. For these purposes it is proposed the representation of the temporal grounding of Spanish modals as a layer within the construal that does not directly affect the implicit character of the modal grounding. It is concluded that temporal grounding should not be considered an obstacle to cognitive analysis and the reason for excluding Spanish modal verbs from the group of grounding elements.